A Transvenous Endovascular Approach in Straight Sinus Has Minor Impacts on Chordae Willisii - Ye, Yuanliang; Ding, Jiuyang; Liu, Shoutang; Lan, Tiancai; Chen, Long; Wang, Yingxue; Xia, Bing; Yang, Jianqing (Frontiers in Neurology, 2022)
Cerebral dural sinuses contain different types of chordae willisii (CW). The transvenous endovascular approach, which has become an optimal method for the treatment of cerebrovascular diseases, such as malformation, fistula, and chronic intracranial hypertension, due to sinus thromboses, frequently uses retrograde navigation through dural sinuses. Whether or how much the endoscopic procedure damages the chordae willisii is often not well-assessed. In our study, an overall number of 38 cadaveric heads were analyzed for the distribution and features of the chordae willisii in the straight sinus. We used an endoscope on these samples mimicking a mechanical thrombectomy procedure performed in the straight sinus. Both endoscopic gross observation and light microscopic histological examination were used to assess the damages to the chordae willisii by the procedure. We found that the valve-like lamellae and longitudinal lamellae structures were mainly found in the posterior part of straight sinus whereas trabeculae were present in both anterior and posterior portions. We treated a group of samples with a stent and another with a balloon. The stent-treated group had a significantly higher rate of Grade 1 damage comparing with the balloon-treated group (p = 0.02). The incidence of damage to the surface of chordae willisii was also higher in the stent-treated group (p = 0.00). Neither the use of stent nor of balloon increased the rate of damage to chordae willisii during repeated experiments. These findings indicated that stent or balloon navigation through the straight sinus can cause minor damages to the chordae willisii and frequent uses of retrograde navigation through the straight sinus do not appear to increase the rates of damage to chordae willisii.